2015
DOI: 10.1016/j.aller.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent advance in investigation of gene polymorphisms in Japanese patients with aspirin-exacerbated respiratory disease

Abstract: Aspirin-exacerbated respiratory disease (AERD) is a complex clinical syndrome characterised by severe asthmatic attack upon treatment with aspirin and/or non-steroidal anti-inflammatory drugs (NSAIDs). Genetic predisposition has been considered as a crucial determinant and candidate genes have concentrated especially on cysteinyl leukotrienes (LTs)-related genes as the inhibitory action of aspirin and NSAIDs on cyclooxygenase activity may cause overproduction of cysteinyl LTs. However, conflicting results have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 91 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…A recent investigation indicated that patients with AERD showed more olfactory loss, but no difference in the total SNOT-22, in comparison with patients without AERD (28). Peripheral blood eosinophil count has been shown to be higher in AERD patients than in aspirin-tolerant asthma (19,29,30). On the other hand, it has been reported that while nasal congestion is a common symptom in patients with eosinophilic CRS, reduction in or loss of the sense of smell precedes nasal congestion (31), and characteristic CT images of the sinuses are opacification of posterior ethomoid sinus and the olfactory cleft (22,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent investigation indicated that patients with AERD showed more olfactory loss, but no difference in the total SNOT-22, in comparison with patients without AERD (28). Peripheral blood eosinophil count has been shown to be higher in AERD patients than in aspirin-tolerant asthma (19,29,30). On the other hand, it has been reported that while nasal congestion is a common symptom in patients with eosinophilic CRS, reduction in or loss of the sense of smell precedes nasal congestion (31), and characteristic CT images of the sinuses are opacification of posterior ethomoid sinus and the olfactory cleft (22,32).…”
Section: Discussionmentioning
confidence: 99%
“…All patients showed that FEV 1 measured with a spirometer was less than 80% of the predicted value for age, sex, and height, with documented short-acting ß 2 agonist reversibility of more than 12% after administration of 180 µg of salbutamol. Six patients (3 each in males and females) were AERD, who were diagnosed as reported (19). Four patients (3 males and 1 female, and 1 AERD male) had been receiving maintenance treatment with oral corticosteroids (5 to 10 mg per day of prednisone or its equivalent) for at least 6 months before entering the study.…”
Section: Patientsmentioning
confidence: 99%
“…The target DNA sequence of SLC6A12 exon 4 T>C was amplified using a set of primers (forward: 5'-TCTTCCCACCAGGCTTTG-3' , reverse: 5'-TCCA-ACTTCTCTCCCTCCTC-3'). Allelic discrimination assay for two SNPs relating to the expressions of SLC6A12 intron 2 A>T and SLC6A12 exon 4 T>C (rs499368 and rs557881, respectively) was carried out by using previously described SNPs detective system, sequence-specific thermal-elution chromatography [9][10][11][12][13][14]. All subjects and investigators remained unaware of the genotype until the final analysis.…”
Section: Genotyping Of Slc6a12 Gene Polymorphismmentioning
confidence: 99%
“…However, conflicting results have been reported [7,8], and other genetic determinants remain to be identified. We have reported some new genetic aspects in Japanese patients with AERD [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…DNA in the specimens obtained by rubbing buccal mucosa with a cotton swab from the patients was extracted by using QIAamp 96 DNA blood kits (Qiagen, Hilden, Germany). The target DNA sequence of the ADRB2 gene NM_000024.4 was amplified using a set of primers that were previously described [15,16] (forward, nucleotides 188-212: 5'-AGCCAGTGCGCTCACCTGCCAGACT-3'; reverse, nucleotides 406-383:5'to generate an amplicon for single nucleotide expression (rs 1042713) sequence-specific thermal-elution chromatography our laboratory [17,18].…”
Section: Patients and Genotyping Of Adrb2 Polymorphismmentioning
confidence: 99%